2020
DOI: 10.31004/obsesi.v5i1.696
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Buku Cerita Bergambar terhadap Pengetahuan Manajemen Bencana Anak

Abstract: Penelitian ini bermaksud membuktikan adanya pengaruh buku cerita bergambar berkaitan dengan pengetahuan manajemen bencana anak. Adapun metode penelitiannya merupakan  eksperimen dengan bentuk quasi eksperimental design. Teknik pengambilan sampel dengan purposive sampling dengan jumlah 48 anak yang berada pada usia 5-6 tahun. Data pengetahuan manajemen bencana anak dikumpulkan dengan menggunakan tes pengetahuan tentang manajemen bencana. Adapun hasil dari studi  ditemukan pengaruh buku cerita bergambar berkenaa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
6
0
4
Order By: Relevance
“…The results of the validation test and several research results, one of which found that picture storybooks were very feasible to be used in learning activities. Research conducted by (Risma et al, 2020) states that picture storybook media is very feasible to be used in learning activities. This is evident from the results of the material expert test obtained by 87.5% and media experts by 96%.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the validation test and several research results, one of which found that picture storybooks were very feasible to be used in learning activities. Research conducted by (Risma et al, 2020) states that picture storybook media is very feasible to be used in learning activities. This is evident from the results of the material expert test obtained by 87.5% and media experts by 96%.…”
Section: Resultsmentioning
confidence: 99%
“…Picture storybooks positively impact early childhood understanding, especially regarding examples of actions following the values of servite et amate (Halim & Munthe, 2019a). The influence of picture story books on children's knowledge of disaster management (Solfiah et al, 2020). The difference between this study and previous studies is that this research develops a children's storybook oriented to Pancasila students' profiles.…”
Section: Introductionmentioning
confidence: 81%
“…Namun hasil wawancara dan observasi dengan jelas menyebutkan bahwa salah satu aspek yang distimulasi adalah perkembangan bahasa. Hal ini sejalan dengan pendapat (Apriza, 2017;Fakhruddin, 2018;Fitriani et al, 2019;Hayati & Suparno, 2020;Purnamasari & Wuryandani, 2019;Rahiem & Widiastuti, 2020;Solfiah et al, 2021;Susanti, 2020;Wahyuni et al, 2020) yang menyatakan bahwa big book dapat menstimulasi berbagai aspek perkembangan seperti kognitif, literasi, berbicara, menyimak/bahasa reseptif, budaya, dan sosialisasi. Para guru juga meyakini bahwa big book yang sengaja dirancang sesuai dengan situasi, kondisi dan tahapan membaca serta topik yang dekat dengan anak dapat digunakan untuk menstimulasi perkembangan anak didik mereka.…”
Section: Rerata Hasil Asesmenunclassified